Spin-Orbit-Coupling Mediated by an Epsilon-Near-Zero Interface - Banzer, Peter; Eismann, Jörg; Ackermann, Lisa; Kantor, B.; Nechayev, S.; Alam, M. Z.; Fickler, R.; Boyd, R. W. (META 2023 Paris - France, 2023)
Taking advantage of a fundamental laws of geometrical optics, i.e., Fresnel equations, allows for coupling polarization and spatial phase degrees of freedom. We show that this conversion of spin to orbital angular momentum can be accomplished by a simple planar, homogeneous, and isotropic layer of an epsilon-near-zero material.
CRIS-Team Scopus Importer:2024-12-16